1989
DOI: 10.1111/j.1464-410x.1989.tb05309.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Extracorporeal Shockwave Lithotripsy Cause Hypertension?

Abstract: Several series have suggested that the incidence of hypertension following extracorporeal shockwave lithotripsy (ESWL) may be as high as 8%. In this study, changes in blood pressure and the incidence of hypertension have been observed in 733 patients 12 to 44 months after renal ESWL on the Dornier HM3. The incidence of hypertension following ESWL was 8.1%. In patients with a pre-ESWL diastolic pressure less than 90 mmHg, the incidence of those with a diastolic greater than or equal to 100 mm Hg post-operativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Nevertheless, when compared to historical controls with an annualized incidence of hypertension between 3 and 6% for males aged 30–60 years, the findings were significant. This report sparked considerable interest and was soon followed by several studies that were supportive of these findings [42, 43, 44, 45, 46] and several reports of surveys that found no changes in blood pressure and no increase in the incidence of hypertension [47, 48, 49, 50, 51]. Williams et al [44] observed patients for 12–21 months after SWL and found that 8% became hypertensive and required treatment.…”
Section: Clinical Swl Adverse Effects: Who Is At Risk?mentioning
confidence: 75%
“…Nevertheless, when compared to historical controls with an annualized incidence of hypertension between 3 and 6% for males aged 30–60 years, the findings were significant. This report sparked considerable interest and was soon followed by several studies that were supportive of these findings [42, 43, 44, 45, 46] and several reports of surveys that found no changes in blood pressure and no increase in the incidence of hypertension [47, 48, 49, 50, 51]. Williams et al [44] observed patients for 12–21 months after SWL and found that 8% became hypertensive and required treatment.…”
Section: Clinical Swl Adverse Effects: Who Is At Risk?mentioning
confidence: 75%
“…There are a few clinical studies reporting an 8% incidence of hypertension secondary to ESWL. 20,31,32 Recently, Janetschek et al reported that eight of nine patients who had hypertension at 26 months after ESWL (patients ≥ 60 years old) had already presented with elevated RI levels immediately after ESWL. 26 The RI levels in all nine hypertensive patients showed a further increase after 26 months, whereas in the majority of normotensive patients a decrease in RI was Table 4 Reported resistive index (RI) changes Bedük et al 22 Kataoka et al 23 Knapp et al 24 observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparison with a normal population is probably not valid since in calcium stone-formers, blood pressure is higher than in normal subjects [42]. In the British study, although the incidence of hypertension following ESWL was 4.9% after a follow-up of 29 months, there was no overall change in the mean blood pressure of the 2 groups (normotensive and hypertensive patients) [36]. Similarly, in four other studies the incidence of hypertension following Urol Int 1999;62:195-200 Bataille/Cardon/Bouzernidj/El Esper/ Pruna/Ghazali/Westeel/Achard/Fournier ESWL varyied from 1.5 to 6% and was insufficient to significantly increase the mean blood pressure [43][44][45][46].…”
Section: Hypertension Onset Following Eswl In Manmentioning
confidence: 69%